Critical Kirchhoff-Choquard system involving the fractional $p$-Laplacian operator and singular nonlinearities - Sang, Yanbin (Topological Methods in Nonlinear Analysis, 2021)
In this paper we study a class of critical fractional $p$-Laplacian Kirchhoff-Choquard systems with singular nonlinearities and two parameters $λ$ and $μ$. By discussing the Nehari manifold structure and fibering maps analysis, we establish the existence of two positive solutions for above systems when $λ$ and $μ$ satisfy suitable conditions.